RISIKO MOSQUITO-BORNE DISEASES PADA WISATAWAN DI INDONESIA DAN PERAN TRAVEL HEALTH NURSING - Putu Ayu Asri Damayanti; Ni Luh Putu Eva Yanti (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2020)
International tourist arrivals increase every year, reaching 1.4 billion tourists in 2019. The increase in tourist visits will increase the risk of tourists experiencing health problems. Health problems for tourists generally originate from diseases transmitted through mosquito bites, known as mosquito-borne diseases (MBD). Malaria, dengue, chikungunya, Japanese encephalitis (JE) and lymphatic filariasis are endemic diseases in Indonesia. Tourists must prepare themselves before traveling to Indonesia and looking for information about the places visited. Travel health nurses carry out travel health services before travel (pre-travel), after travel (post-travel), and during travel (during / in-transit care) by focusing on primary and secondary prevention of diseases related to travel. Prevention of mosquito bites and chemoprophylaxes is an effective preventive measure because most MBD does not vaccine preventable diseases except for JE. The travel health nursing is needed to prepare and monitor the health of tourists.